Potential medicinal herb for cardiovascular health : a comprehensive review on Salviae miltiorrhizae - Ng, Ting Wei; Tan, Paulina Pei Suu; Lim, Hooi Min; Devaraj Navin Kumar,; Shamsul Mohd Zain,; Low, Teck Yew; Pung, Yuh-Fen (Penerbit Universiti Kebangsaan Malaysia, 2022)
Cardiovascular disease (CVD) and its associated risk factors have been ranked the number 1 cause of mortality in noncommunicable diseases worldwide and Malaysia. The high statistic in CVD mortality indicates gaps and limitations in current treatment strategies using long-term drug prescription therapies. Hence, an immediate quest for alternative and effective treatments is needed. Medicinal herbs, which are ethnopharmacologically used to treat a wide range of conditions, have been used as an alternative or supplementary treatment for CVDs and their associated risk factors. The roots of Salviae miltiorrhizae have been traditionally used for centuries to treat various diseases including neurological disorders, cancer, and even coronary heart disease. Increasing evidence demonstrated a pharmacological basis for the action of S. miltiorrhizae and its active compounds, suggesting its potential in treating CVD. The objectives of this review were first to summarize published literature and synthesize the new body of knowledge on the use of S. miltiorrhizae as the potential medicinal herb that will positively impact the cardiovascular system, and secondly to elucidate the underlying mechanisms involved in promoting cardiovascular health. It is hoped that identification of key regulatory pathways by lipophilic and hydrophilic active compounds from S. miltiorrhizae will aid further investigation of its safety and efficacy to promote the use of evidence-based traditional medicinal herbs in alleviating symptoms and improve the prognosis of CVDs and their associated risk factors.